Factors associated with long-acting family planning service utilization in Ethiopia: a systematic review and meta-analysis - Tamirat Tesfaye Dasa; Teshager Worku Kassie; Aklilu Abrham Roba; Elias Bekele Wakwoya; Henna Umer Kelel (BMC, 2019)
Abstract Background Even though the modern contraceptive use was improved in Ethiopia, the utilization of long-acting family planning services is still low because of numerous factors. The aim of this systematic review was to synthesize logical evidence about factors associated with long acting family planning service utilization in Ethiopia. Methods The participants of the study were married women of reproductive age in Ethiopia. This search included all published and unpublished observational studies written in the English language conducted before April 30, 2018, in Ethiopia. Electronic and non-electronic sources were used. PubMed, MEDLINE (EBSCO), CINHAL (EBSCO), Embase (EBSCO), POPLINE and the search engines like Google, Google Scholar Mednar and world cat log were used. The overall selected search results were 15 studies. Each study was evaluated using the Joanna Briggs Institute Quality Assessment Tool for Observational Studies. Data synthesis and statistical analysis were conducted using ReviewManagerVersion5.3.5. Results Women's inadequate knowledge level [OR, 0.29; 95% CI: 0.10, 0.83, P = 0.02], women's age between 15 and 34 [OR, 0.82; 95% CI: 0.53, 0.93, P = 0.01], not having electronic media [OR, 0.65; 95% CI: 0.53, 0.79, P < 0.0001] and women from rural area [OR = 0.65;95% CI:0.50, 0.81, P = 0.0009] were less likely associated in the use of long-acting family planning services. The odds of utilizing long acting family planning methods were high among non-government- employed women and husband [OR, 1.77; 95% CI: 1.29, 2.43, P = 0.0004], [OR, 1.69; 95% CI: 1.33, 2.15, P < 0.0001] respectively. Having no previous exposure to any modern family planning method [OR = 2.29; 95%CI: 1.83, 2.86, P < 0.00001] and women having no discussion with husband [OR = 1.92 (95%CI: 1.50, 2.45) P < 0.00001] were more likely associated in the utilization of long-acting family planning services. Conclusion Lack of information and knowledge, having discussion with husband, being women of younger age, having less than five living children, being government-employed women and husband, not having electronic media, and being residents in rural area were significant barriers for underutilization of long acting family planning methods in Ethiopia. Hence, the investigators suggest that key stakeholders should design interventions strategies to avert attitudinal, cultural and informational barriers towards long-acting family planning methods. Systematic review registration PROSPERO: 2018: CRD42018096373.